Mitochondrial Function in Gilles de la Tourette Syndrome Patients With and Without Intragenic IMMP2L Deletions - Bjerregaard, Victoria A.; Schönewolf-Greulich, Bitten; Juel Rasmussen, Lene; Desler, Claus; Tümer, Zeynep (Frontiers in Neurology, 2020)
Background: Gilles de la Tourette syndrome (GTS) is a neurodevelopmental condition characterized by motor and vocal tics. The underlying etiology remains largely unknown; and GTS is considered as a complex multifactorial disorder associated with effects of several genes in combination with environmental factors. IMMP2L (inner mitochondrial membrane peptidase, subunit 2), has been suggested as one of the susceptibility genes for GTS; and IMMP2L deficient mouse and human cells show increased levels of mitochondrial oxidative stress and altered cell fate programming. Hence, a potential involvement of IMMP2L-induced mitochondrial dysfunction in GTS pathology is yet to be elucidated. To address this, we investigated mitochondrial function in a group of GTS patients with and without intragenic IMMP2L deletions. Methods: Mitochondrial function in fibroblast from GTS patients (with and without IMMP2L deletions) and from healthy controls were evaluated by measuring mitochondrial superoxide production, mitochondrial membrane potential, mitochondrial mass and mitochondrial respiration. In addition, we evaluated apoptosis and senescence. Results: None of the mitochondrial parameters assessed in this study were significantly distinctive when comparing GTS patients, and healthy controls; and we did not observe altered cell programming. Conclusion: This study suggests that IMMP2L deletions do not lead to a substantial general mitochondrial dysfunction in GTS fibroblasts. Assessing a large cohort of controls and patients of similar age and gender would possibly reveal small differences in mitochondrial function. Furthermore, it is possible that IMMP2L variants affect mitochondrial function during specific instances of stress stimuli or in brain regions suggested to be affected in GTS.